Development of Indonesian Language Learning Media Based on Learning Cycle 5E Using Adobe Animate Software on Reading and Reading Comprehension Material for Grade 3 Elementary School - Ratnasari, Dine Trio; Deby Fauzi Asidiqi; Yuyun Yuningsih; Dede Kurnia Adiputra; Yadi Heryadi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study aims to (1) describe the specifications of Indonesian language learning media based on Learning Cycle 5E using Adobe Animate software on Reading and understanding reading materials for grade 3 elementary school that were developed and (2) describe the results of expert assessments, peer reviewers, education practitioners, and students from Indonesian language learning media based on Learning Cycle 5E using Adobe Animate software on Reading and understanding reading materials for grade 3 elementary school that were developed and reviewed from the aspects of software engineering, learning design, and visual communication . The research method used is the development method with a 4-D model consisting of four stages, namely the define, design, develop, and disseminate stages. The data used are qualitative and quantitative data. The data sources in this study were two experts, five peer reviewers (students), three education practitioners (teachers), and 100 elementary school students in Lebak Regency. Data collection techniques used questionnaire and interview techniques. Data analysis used the trait category carried out by Azwar. The conclusions that can be drawn from this study are (1) the specifications of the media developed have 4 menus, namely information, competence, material, exciting reading, and evaluation. The information menu contains instructions for using media, learning media developers, reference sources. The competency menu contains core competencies, basic competencies, competency achievement indicators, concept maps, competency maps. The material menu contains 2 sub-materials, namely fictional reading material and non-fiction reading material. The evaluation menu contains 25 multiple-choice questions that can be worked on via office forms with a time of 40 minutes. The application is 78 MB in size and can be accessed offline and online. (2) Learning media based on Learning Cycle 5E using Adobe Animate software on reading and reading comprehension materials meets the criteria of very good based on aspects of software engineering, learning design, and visual communication reviewed from the results of expert validation, peer reviewers, education practitioners, and students.